A new cation‐modified Al‐polyacrylamide flocculant for solid–liquid separation in waste drilling fluid. Issue 11 (8th November 2014) - Zhang, Yongming; Miao, Zongcheng; Zou, Jing
ABSTRACT A new cation‐modified Al‐polyacrylamide (CAPAM) flocculant was prepared by the in situ polymerization of acrylamide (AM) and (2‐methacryloyloxyethyl) trimethyl ammonium chloride (DMC) with Al(OH)3 sol. The optimum preparation conditions were obtained by a one‐factor experimental design: as the amount of AlCl3 was fixed at 0.025 mol, the polymerization time, polymerization temperature, n(AM) : n(AlCl3), n(DMC) : n(AlCl3), and n(K2S2O8) : n(AM) were 4 h, 70°C, 8, 0.9, and 1.82 × 10−3, respectively. The CAPAM was characterized by thermogravimetric analysis, Fourier transform infrared spectroscopy, scanning electron microscopy, and transmission electron microscopy. The solid–liquid separation performance of the CAPAM was evaluated in terms of water content. The CAPAM showed better flocculation performance than cationic polyacrylamide and polyaluminum sulfate at a fixed concentration of 0.3% in waste drilling fluid and tended to perform well in alkaline solution. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41641.